2000
DOI: 10.1002/1097-4644(2000)79:1<89::aid-jcb90>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen influences cartilage calcification: An immunoblocking study in differentiating chick limb-bud mesenchymal cell cultures

Abstract: Chick limb-bud mesenchymal cells, plated in high-density micro-mass culture, differentiate and form a matrix resembling chick epiphyseal cartilage. In the presence of 4 mM inorganic phosphate or 2.5 mM beta-glycerophosphate mineral deposits upon this matrix forming a mineralized tissue that, based on electron microscopy, x-ray diffraction and Fourier Transform Infrared microspectoscopy, is like that of chick calcified cartilage. In this culture system the initial mineral deposits are found on the periphery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
See 4 more Smart Citations
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
“…Chick limb-bud mesenchymal cells plated in high-density micromass cultures differentiate to form a mineralizable matrix that resembles the growth plate in the chick [18][19][20][21][22][23][24][25][26]. Our earlier studies using 2,3-diphosphoglycerate and heparin, both non-specific inhibitors of CK2, showed inhibition of mineralization when protein phosphorylation was blocked [18].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations